2019
DOI: 10.3390/polym11091394
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Amino Resin-based Photosensitive Materials on Multi-parameter Optimization Design for Vascular Engineering Applications

Abstract: Cardiovascular diseases are currently the most common cause of death globally and of which, the golden treatment method for severe cardiovascular diseases or coronary artery diseases are implantations of synthetic vascular grafts. However, such grafts often come with rejections and hypersensitivity reactions. With the emergence of regenerative medicine, researchers are now trying to explore alternative ways to produce grafts that are less likely to induce immunological reactions in patients. The main goal of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…Current studies state that pores with a size of up to 500-750 µm were critical for bone tissue regeneration and growth. Different cell lines require different pore sizes; however, pores were found to be critical as they provide contact points for cells to adhere to, and it was further reported that efficient initial adhesion allows enhanced subsequent downstream cellular activities and behaviors, such as enhanced cellular proliferation and tissue regeneration [31].…”
Section: Discussionmentioning
confidence: 99%
“…Current studies state that pores with a size of up to 500-750 µm were critical for bone tissue regeneration and growth. Different cell lines require different pore sizes; however, pores were found to be critical as they provide contact points for cells to adhere to, and it was further reported that efficient initial adhesion allows enhanced subsequent downstream cellular activities and behaviors, such as enhanced cellular proliferation and tissue regeneration [31].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, a deformed polymer shape-changed by light irradiation is also able to temporarily retain its shape even after the external stimulus is removed. By applying certain wavelength of light, photo-sensitive cross-links are cleaved or formed, thus allowing polymers to retain or return to their intended shapes [18].…”
Section: Introductionmentioning
confidence: 99%
“…DLP uses a photo-polymerization technique to cross-link photo-curable materials according to your computer-aided design (CAD). When the photo-curable bio-ink absorbs the ultra-violet (UV) ray, it generates active radicals or ionic groups, which in turn leads to the subsequent reaction of polymer polymerization and cross-linking [21]. Three-dimensional structure stereoscopic scaffold within a range of micrometers to nanometers can be prepared using DLP as it uses the light source as its curing energy [22].…”
Section: Introductionmentioning
confidence: 99%